Exploring similarities and differences in anti-atherosclerotic potential bioactives among Dendrobium species by UPLC-Q-Exactive Orbitrap MS - Yu Zhang; Xi Chen; Oushan Tang; Keyun Cheng; Lijun Ge; Weibo Lu; Jing Zheng; Yeshun Wu; Si-wei Wang; Xi-xi Zeng; Jing Xue; Yiwei Cui; et al. (npj Science of Food)
Abstract Atherosclerosis is a primary cause of cardiovascular disease, straining healthcare systems. Dendrobium officinale, a widely used food-medicine homology, has demonstrated anti-atherosclerotic (anti-AS) properties, with other species listed in pharmacopoeias exhibiting similar effects. However, their efficacy varies, and the impact of interspecies variations on compounds and mechanisms in Dendrobium’s anti-AS effects remains unclear. This study aimed to explore the anti-AS compounds and mechanisms across various Dendrobium species. The chemical composition of D. fimbriatum, D. officinale, D. devonianum, D. gratiosissimum, and D. catenatum was analyzed using UPLC-Q-Exactive Orbitrap MS. Network pharmacology predicted the pharmacological basis and molecular mechanisms. Molecular docking experiments assessed the binding affinity of the identified compounds with target proteins. A total of 12 different and 65 common components were identified. Key therapeutic targets included SRC, STAT3, and PIK3CA, along with relevant signaling pathways linked to AS prevention. The study provides insights into interspecies differences in Dendrobium’s anti-AS properties.